Pemanfaatan Green Marketing Oleh Usaha Mikro, Kecil, dan Menengah (UMKM) Kuliner Berbasis Lokal di Kota Bandung - Diva Ayu Pertiwi; Sefti Afrillia; Zakia Anggraini; Oki Iqbal Khair (Journal Economic Excellence Ibnu Sina, 2025)
The increasing consumer awareness of environmental issues has encouraged culinary Micro, Small, and Medium Enterprises (MSMEs) to adopt green marketing strategies as an effort to build competitive advantage. Bandung City, as a creative city with strong local culinary potential, is the focus of this study to analyze the implementation of green marketing in the MSME culinary sector. This study aims to analyze the utilization of green marketing by local-based culinary MSMEs in Bandung, identify the driving and inhibiting factors of its implementation, and measure its impact on business performance. The research applied a qualitative approach by conducting a survey with 150 culinary MSMEs and in-depth interviews with 20 business owners. The findings indicate that 68% of MSMEs have implemented at least one green marketing element, focusing primarily on the use of environmentally friendly packaging (72%) and local raw materials (65%). The main driving factors were consumer demand (78%) and government regulations (56%), while the primary barriers included limited capital (65%) and lack of knowledge (58%). Although the implementation of green marketing among culinary MSMEs in Bandung is still in its early stages, the trend is positive. Government and institutional support is needed to enhance MSMEs’ capacity in developing sustainable marketing strategies.